The role of neurofilament light chain in the context of neurological disorders - Taluntienė , V.; Motiekaitytė , R.; Kizlaitienė , R.; Giedraitienė , N.; Kaubrys , G. (Neurologijos seminarai, 2020)
Neurofilament light chain (NFL) is a structural neuronal protein highly expressed in large myelinated axons. Axonal damage leads to increased NFL levels in cerebrospinal fluid and blood. Therefore, it could be a potential diagnostic biomarker for various neurological disorders, especially caused by neurodegeneration and inflammation. New sensitive immunoassays for NFL measurement in the blood offer possibilities of monitoring disease progression and assessing treatment response. An increasing amount of data suggests that NFL could also be a prognostic marker for many disorders. The purpose of this article is to review the literature on the role of NFL in the context of dementia, amyotrophic lateral sclerosis, HIV-associated neurocognitive disorders, multiple sclerosis, and other neurological diseases.
Keywords: neurofilament light chain; axonal damage; neurodegeneration; multiple sclerosis